2018
DOI: 10.1371/journal.pone.0191170
|View full text |Cite
|
Sign up to set email alerts
|

Slightly increased BMI at young age is a risk factor for future hypertension in Japanese men

Abstract: BackgroundHypertension is developed easily in Asian adults with normal body mass index (BMI) (~23 kg/m2), compared with other ethnicities with similar BMI. This study tested the hypothesis that slightly increased BMI at young age is a risk factor for future hypertension in Japanese men by historical cohort study.MethodsThe study participants were 636 male alumni of the physical education school. They had available data on their physical examination at college age and follow-up investigation between 2007 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
3
16
0
3
Order By: Relevance
“…Men with high BMI and low aerobic capacity were associated with highest risk to develop hypertension in adulthood (Crump et al, 2016). In addition, a 27-year follow-up study which included 17059 Japanese men revealed that risk of incident hypertension positively and significantly increased with an increased BMI (Someya et al, 2018). This study suggested that the overweight BMI inflection point for vascular diseases among Japanese men was >23 kg/m 2 which was similar to the BMI cut-off used in our study (Someya et al, 2018).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Men with high BMI and low aerobic capacity were associated with highest risk to develop hypertension in adulthood (Crump et al, 2016). In addition, a 27-year follow-up study which included 17059 Japanese men revealed that risk of incident hypertension positively and significantly increased with an increased BMI (Someya et al, 2018). This study suggested that the overweight BMI inflection point for vascular diseases among Japanese men was >23 kg/m 2 which was similar to the BMI cut-off used in our study (Someya et al, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, a 27-year follow-up study which included 17059 Japanese men revealed that risk of incident hypertension positively and significantly increased with an increased BMI (Someya et al, 2018). This study suggested that the overweight BMI inflection point for vascular diseases among Japanese men was >23 kg/m 2 which was similar to the BMI cut-off used in our study (Someya et al, 2018). In men, BMI is positively associated with risk of incident hypertension.…”
Section: Discussionsupporting
confidence: 78%
“…Por sua vez, à utilização desses indicadores, tanto o IMC quanto a CC, poderiam ser úteis nos ambientes de academias de ginástica. Essa afirmação é corroborada por estudos anteriores que demonstraram associações desses indicadores antropométricos com a HA 24,25,26,27 .…”
Section: Discussionunclassified
“…Diferenças nos potenciais explicativos de IMC e CC associados a HA são encontradas em revisões anteriores 24,25 , e o conhecimento por parte dos profissionais envolvidos na avaliação física de academias sobre essas diferenças é de suma importância. Além disso, cada vez mais pessoas tem procurado o serviço de academias 28 , principalmente as que apresentam excesso de peso.…”
Section: Discussionunclassified
“…The anthropometric, physical tness tests and motor ability tests are implemented once per year at the university over the four years of university studies. The J-Fit Study is a project that uses the accumulated 50 years of data collected as indicated above for research into the association between physical tness, motor ability at a young age and future diseases, such as diabetes, type 2 diabetes, and hypertension [15][16][17][18]. In the present study, we used data obtained from tests results of subjects in their fourth year at university.…”
Section: Study Design and Populationmentioning
confidence: 99%